Analysis of admixture and genetic structure of two Native American groups of Southern Argentinean Patagonia - Sala, Adriana Andrea (2014)
Argentinean Patagonia is inhabited by people that live principally in urban areas and by small isolated groups of individuals that belong to indigenous aboriginal groups; this territory exhibits the lowest population density of the country. Mapuche and Tehuelche (Mapudungun linguistic branch), are the only extant Native American groups that inhabit the Argentinean Patagonian provinces of Río Negro and Chubut. Fifteen autosomal STRs, 17 Y-STRs, mtDNA full length control region sequence and two sets of Y and mtDNA-coding region SNPs were analyzed in a set of 434 unrelated individuals. The sample set included two aboriginal groups, a group of individuals whose family name included Native American linguistic root and urban samples from Chubut, Río Negro and Buenos Aires provinces of Argentina. Specific Y Amerindian haplogroup Q1 was found in 87.5 % in Mapuche and 58.82 % in Tehuelche, while the Amerindian mtDNA haplogroups were present in all the aboriginal sample contributors investigated. Admixture analysis performed by means of autosomal and Y-STRs showed the highest degree of admixture in individuals carrying Mapuche surnames, followed by urban populations, and finally by isolated Native American populations as less degree of admixture. The study provided novel genetic information about the Mapuche and Tehuelche people and allowed us to establish a genetic correlation among individuals with Mapudungun surnames that demonstrates not only a linguistic but also a genetic relationship to the isolated aboriginal communities, representing a suitable proxy indicator for assessing genealogical background.